Registration Application Services for BPJS Patients at Hutabaginda Primary Healthcare - Situmorang, Benri; Sansuwito, Tukimin Bin; Dioso, Regidor III; Herlina, Herlina; Nainggolan, Nurcahaya (PT. Riset Press International, 2024)
Primary Healthcare is one of the most important health service units in health services that are adapted to local government conditions, needs, requirements and regulations. Recording data at the Primary Healthcare manually takes a long time. When a patient forgets to bring a medical card, it takes a long time to get the file which results in a long time in the registration service process, if the file is not found it is necessary to create a new file. will be automatically created, resulting in duplication of data. Most patients forget to bring their medical card when they want to take it. In addition, when making monthly reports, officials must record data one by one as a monthly report. The use of this application is to increase the effectiveness of the information system for the patient registration Primary Healthcare based on the website and the BPJS application called JKN BPJS.